#TITLE_ALTERNATIVE# - (NIM 234 03 014), Usman
Abstract: IS function defined as all individuals, group, or department in an organization that is daily responsible in developing and supporting the operation of organizational information system. Relevance with increase of IS budget and dependence of organization performance to IS function performance, measurement of IS function performance is getting more important. Measurement instrument of IS function can be used to measure strength and weakness of certain dimensions in IS area, to benchmark internal company, and also be used to identify strength and weakness among divisions/departments in company. This research purposes to have a result of IS function performance measurement scorecard. Start from the definition of IS function, produced 4 main dimensions of IS function performance measurement, - product quality, service quality, capability, and net benefit. By literature study in the areas of IS success, organizational effectiveness, IS resources and capability, and IS function performance, identified 66 items of IS function performance measurement for the four main dimensions. 91 samples of this research obtained from 26 organizations in national and multinational scale merely in state own enterprise and go public company used to validate the constructs of measurement items. Using exploratory factor analysis extracted 16 factors for the four main dimensions. By using structural equation model in confirmatory factor analysis iteratively, tested the validity and reliability of the measurement items and to establish their unidimensionality. Result of the analysis argues that 20 measurement items of the four factors are valid and reliable indicators to measure the constructs of product quality, 14 measurement items of the four factors are valid and reliable indicators to measure the constructs of service quality, 8 measurement items of the three factors are valid and reliable indicators to measure the constructs of capability, 19 measurement items of the five factors are valid and reliable indicators to measure the constructs of net benefit.